Kepemilikan Asing dan Nilai Perusahaan di PT. Bursa Efek Indonesia - Taufik Taufik; Dian Eka (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2010)
This  research aims to investigate how foreign ownership influence on firm value of 2004-2008 at firm manufacturing sectors of the Indonesian stock exchange based on firms with 1% to less than 20% foreign ownership, 20% to less than 50% foreign ownership and up to 50% foreign ownership. Purposive sampling has been carried out in this research. Of 173, only 54 firms can be taken out. From 54 sample firms, 20 firms were taken as firms with 1% to less than 20% foreign ownernership, 17 firms with 20% to less than 50% foreign ownership and 17 firms up to 50% foreign ownership. Linier regression was implemented in this research to see the influence of foreign ownership to firm value. This research also includes firm size and firm growth as control variables. I was found that firm size, firm growth and foreign ownership were a positive and significant influence on firm value with 1% to less than 20% of foregn ownership. As the level of foreign ownership increased 20% to less than 50%, only firm size and firm growth were a positive and significant influence on firm value while foregn ownership was a negative influence. When the level of foreign ownership was up to 50%, firm size, firm growth and foreign ownership were a positive and significant influence on firm value. Since there is limitation on this research, further research is recommended to include other variables influencing firm value.Keywords: Foreign ownership, Firm Value, Firm Size, firm growth